Innovation to Increase Palm Sugar Production into Ant Sugar Coffee - Hidayat, Gustina; kartiwa, Aa; Deliasari, Syifa; Sihombing, Lusiana (Almana : Jurnal Manajemen dan Bisnis, 2025)
Palm sugar is one of the leading products of Citengah Village, Sumedang Regency, this innovation aims to process palm sugar into ant sugar coffee, which is an instant product in the form of dry crystals resulting from a combination of palm sugar and coffee powder. The method used was a household-scale experiment with stages: cooking of palm sugar solution, mixing of local coffee grounds, crystallization, and drying at 90–100°C. The results showed that the product had a smooth crystalline shape, dark brown color, a distinctive aroma of coffee and palm sugar, and was easily dissolved in hot water. Organoleptic tests on 20 respondents showed a preference level of 85%, especially in taste and aroma. This product also has a shelf life of more than three months without preservatives. The innovation of ant sugar coffee not only increases the added value of local palm sugar, but also opens up new market opportunities for natural instant drink products. It is hoped that this product can be an alternative to typical Sumedang souvenirs while supporting the economic empowerment of the village community.